Pengaruh Kualitas Produk, Harga dan Promosi Terhadap Loyalitas Pelanggan Melalui Kepuasan Pelanggan Pada Konsumen Tabletop Board Game Cafe - Tya Wildana Hapsari Lubis; Jesica; Valencia; Fitria Halim (Jurnal Wira Ekonomi Mikroskil, 2025)
This study aims to determine the effect of product quality, price, and promotion on customer loyalty, with customer satisfaction as an intervening variable. This study was conducted among TableTop Board Game Cafe customers. The dependent variable, customer loyalty (Y), was mediated by the intervening variable (Z), and the independent variables were product quality (X1), price (X2), and promotion (X3). This study used a quantitative approach with a non-probability sampling technique involving 100 respondents. Data processing was performed using SmartPLS 4.0 software. The results showed that product quality, price, and promotion did not have a significant direct effect on customer loyalty. However, all three variables significantly influenced customer satisfaction. Customer satisfaction was shown to have a significant direct effect on customer loyalty.